LITERATURE STUDY OF THE DYNAMICS OF INDONESIAN HALAL CERTIFICATION - Nirmadarningsih Hiya; Zuhrinal M. Nawawi (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study examines research related to “Halal Certification” in national journal articles. Using descriptive statistical analysis and narrative review of 18 publication articles related to "Halal Certification". All articles used as samples have been published. The results show that research related to Halal Certification discusses more about the regulation of the application of halal certification as many as 6 articles (33%), then discusses how the halal certification process as much as 5 articles (28%) followed by a discussion of the impact of halal certification on the economy and socialization of each 4 and 3 articles respectively. The research approach used in the article under study as a whole uses a qualitative approach.